Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review. - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatr Exerc Sci)

Entstehen durch eine Blicktäuschung Kosten für den Angreifer? - Güldenpenning, Iris; Weigelt, Matthias; Kunde, W. (Abstractband der 51. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Die Blicktäuschung im Basketball: Einfluss des zeitlichen Versatzes zwischen Blick- und Kopfwendung auf den Täuschungseffekt - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstractband der 51. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Deceptive Actions - Güldenpenning, Iris; Weigelt, Matthias (Dictionary of Sport Psychology)

A General Algorithm to Calculate the Inverse Principal p-th Root of Symmetric Positive Definite Matrices - Richters, Dorothee; Lass, Michael; Walther, Andrea; Plessl, Christian; Kühne, Thomas (Communications in Computational Physics)
We address the general mathematical problem of computing the inverse p-th root of a given matrix in an efficient way. A new method to construct iteration functions that allow calculating arbitrary p-th roots and their inverses of symmetric positive definite matrices is presented. We show that the order of convergence is at least quadratic and that adaptively adjusting a parameter q always leads to an even faster convergence. In this way, a better performance than with previously known iteration schemes is achieved. The efficiency of the iterative functions is demonstrated for various matrices with different densities, condition numbers and spectral radii.

Inklusion im Nachwuchsleistungssport. Vereinbarkeit von Schule und paralympischem Leistungssport an Eliteschulen des Sports versus Regelschulen.

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat J. (physica status solidi (b))

Erwerb motorischer und sensorischer Kompetenzen - Krause, Daniel; Ramme, Katharina; Weigelt, Matthias (Praktische Ausbildung in der Physiotherapie)

Stereoselective Alkyne Hydrogenation by using a Simple Iron Catalyst - Gregori, Bernhard J.; Schwarzhuber, Felix; Pöllath, Simon; Zweck, Josef; Fritsch, Lorena; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Digitalisierung im organisierten Sport – Eine Analyse zur Nutzung digitaler Instrumente in Sportvereinen - Riedl, Lars; Ehnold, Peter; Schlesinger, Torsten (Sciamus - Sport und Management, 4)
Trotz hoher Aktualität und steigender Bedeutung liegen zum Thema Digitalisierung im Sportverein bisher kaum empirische Erkenntnisse vor. Der vorliegende Beitrag setzt sich mit folgenden Fragestellungen auseinander: (i) In welchem Umfang und zu welchem Zweck nutzen Sportvereine digitale Instrumente? (ii) Welche vereinsspezifischen Faktoren determinieren das jeweilige Nutzungsverhalten? Hierzu wurde eine Stichprobe von n=787 Sportvereinen aus Österreich und Deutschland generiert. Es zeigt sich, dass digitale Instrumente vor allem zur internen und externen Kommunikation sowie zur Bewältigung klassischer Verwaltungsaufgaben eingesetzt werden. Das Ausmaß der Nutzung hängt einerseits von vereinsexternen Bedingungen ab. So zeigt sich dahingehend ein Ländereffekt, dass in Deutschland digitale Instrumente stärker genutzt werden als in Österreich. Darüber hinaus haben Auflagen seitens der Verbände zur Verwendung bestimmter Software (z.B. für die Meldung von Wettkampfergebnissen) einen wichtigen Einfluss. Andererseits bestimmen vereinsinterne Faktoren wesentlich das Nutzungsverhalten. Positiv wirken vor allem die Vereinsziele ‚Engagement/Erfolg im Leistungssport‘ und ‚Wollen Vorreiterrolle bei der Digitalisierung einnehmen‘. Negativ wirken eine fehlende Strategie im Umgang mit digitalen Instrumenten sowie die Einschätzung, dass digitale Prozesse nicht zur eigenen Vereinskultur passen.

Die Funktion des Sports im Gesundheitsmanagement der öffentlichen Verwaltung - Sennefelder, Lisa

Hard X-ray spectroscopy: an exhaustive toolbox for mechanistic studies (?) - Schoch, Anke; Burkhardt, Lukas; Schoch, Roland; Stührenberg, Kai; Bauer, Matthias (Faraday Discussions)
The hard X-ray spectroscopy methods XAS, valence-to-core XES and higher solution XANES offer unique insights into organometallic reaction mechanisms.

Kompetenzorientierte, universitäre Laborpraktika - Das Paderborner Physik Praktikum (3P) - Bauer, Anna; Sacher, Marc (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

Operationalisierung der experimentellen Kompetenz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Qualitätsvoller Chemie- und Physikunterricht – normative und empirische Dimensionen)

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg K. N.; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)

Easily Accessible Protein Nanostructures via Enzyme Mediated Addressing - Rüdiger, Arne A.; Brassat, Katharina; Lindner, Jörg K. N.; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)

Using Approximate Computing for the Calculation of Inverse Matrix p-th Roots - Lass, Michael; Kühne, Thomas; Plessl, Christian (Embedded Systems Letters)
Approximate computing has shown to provide new ways to improve performance and power consumption of error-resilient applications. While many of these applications can be found in image processing, data classification or machine learning, we demonstrate its suitability to a problem from scientific computing. Utilizing the self-correcting behavior of iterative algorithms, we show that approximate computing can be applied to the calculation of inverse matrix p-th roots which are required in many applications in scientific computing. Results show great opportunities to reduce the computational effort and bandwidth required for the execution of the discussed algorithm, especially when targeting special accelerator hardware.

Habitual Fructose Intake Relates to Insulin Sensitivity and Fatty Liver Index in Recent-Onset Type 2 Diabetes Patients and Individuals without Diabetes. - Weber, KS; Simon, MC; Strassburger, K; Markgraf, DF; Buyken, Anette; Szendroedi, J; Müssig, K; Roden, M; Group, GDS (Nutrients)

Body dissatisfaction in normal weight children – Sports activities and motives for engaging in sports - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J.; Trojan, J. (European Journal of Sport Science)

Dietary carbohydrates: a review of international recommendations and the methods used to derive them. - Buyken, Anette; Mela, DJ; Dussort, P; Johnson, IT; Macdonald, IA; Stowell, JD; FJPH, Brouns (Eur J Clin Nutr)

Caring, Cooking, Cleaning – repräsentative Zeitverwendungsmuster von Eltern in Paarbeziehungen - Klünder, Nina; Meier-Gräwe, Uta (Journal of Family Research)
As a result of the increasing labor force participation of mothers, this article questions how twoparent households divide the housework activities of caring, cooking and cleaning. Therefore three types of couples with different labor force participations were formed: Dual-earner couples, couples with additional female income and malebreadwinner couples. The time use for the mentioned activities was examined with a secondary analysis based on the German representative time use surveys of 2012/2013 and 2001/2002. The analysis showed that fulltime mothers spent the lowest amount of time for caring, cooking and cleaning. However, unemployed mothers spent the most time for these activities. Within a decade – from 2001/2002 to 2012/2013 – all mothers have reduced their time spent on household activities. Meanwhile, all parents in 2012/2013 take noticeably more time for child care. Regardless of the mother’s labor force participation, mothers still spent more time for caring, cooking and cleaning, especially on weekdays. Additionally, the everyday housework is divided by gender. Only on weekends, couples with employed mothers shared the care-work almost egalitarian.
Zusammenfassung
Vor dem Hintergrund der steigenden Erwerbstätigkeit von Müttern geht dieser Beitrag der Frage nach, wie Eltern in Paarbeziehungen die Haushaltsbereiche Betreuung, Beköstigung sowie Wohnungs- und Wäschereinigung untereinander aufteilen. Dazu werden drei Paartypen mit unterschiedlichem Erwerbsumfang gebildet: Zweiverdiener- Paare, Paare mit weiblichem Zuverdienst sowie Paare mit männlichem Familienernährer. Deren Zeitverwendung für die genannten Tätigkeiten wird mithilfe der repräsentativen Zeitverwendungserhebung 2012/2013 und 2001/2002 sekundäranalytisch untersucht. Die Analyse zeigt, dass vollzeiterwerbstätige Mütter täglich am wenigsten Zeit für die drei genannten Arbeitsbereiche im Haushalt aufwenden, nicht erwerbstätige Mütter hingegen am meisten. Innerhalb einer Dekade – von 2001/2002 bis 2012/2013 – haben alle untersuchten Mütter ihre Zeitverwendung für hauswirtschaftliche Tätigkeitsfelder reduziert, zeitgleich nehmen sich Eltern 2012/2013 deutlich mehr Zeit für Betreuungsaufgaben. Unabhängig des Erwerbsumfangs der Mutter ist die Arbeit des Alltags nach wie vor, besonders werktags, weiblich konnotiert und somit geschlechtsdifferenzierend aufgeteilt. Nur am Wochenende zeigt sich in Paaren mit erwerbstätiger Mutter bei der Betreuung eine annährend egalitäre Arbeitsteilung.

Zwischen selbst Gekochtem, Thermomix und Schulverpflegung – Innenansichten der Ernährungsversorgung von Familien mit erwerbstätigen Eltern - Klünder, Nina (Hauswirtschaft und Wissenschaft)

Relation of dietary glycemic index, glycemic load, added sugar intake, or fiber intake to the development of body composition between ages 2 and 7 y - Buyken, Anette; Cheng, Guo; Günther, Anke LB; Liese, Angela D; Remer, Thomas; Karaolis-Danckert, Nadina (The American Journal of Clinical Nutrition)

Flavonoid intake from fruit and vegetables during adolescence is prospectively associated with a favourable risk factor profile for type 2 diabetes in early adulthood - Penczynski, Katharina J.; Herder, Christian; Krupp, Danika; Rienks, Johanna; Egert, Sarah; Wudy, Stefan A.; Roden, Michael; Remer, Thomas; Buyken, Anette (European Journal of Nutrition)

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)
DNA origami nanostructures are versatile substrates for the controlled arrangement of molecular capture sites with nanometer precision and thus have many promising applications in singlemolecule bioanalysis. Here, we investigate the adsorption of DNA origami nanostructures in nanohole arrays which represent an important class of biosensors and may benefit from the incorporation of DNA origami-based molecular probes. Nanoholes with well-defined diameter that enable the adsorption of single DNA origami triangles are fabricated in Au films on Siwafers by nanosphere lithography. The efficiency of directed DNA origami adsorption on the exposed SiO2 areas at the bottoms of the nanoholes is evaluated in dependence of various parameters, i.e., Mg2+ and DNA origami concentrations, buffer strength, adsorption time, and nanohole diameter. We observe that the buffer strength has a surprisingly strong effect on DNA origami adsorption in the nanoholes and that multiple DNA origami triangles with 120 nm edge length can adsorb in nanoholes as small as 120 nm in diameter. We attribute the latter observation to the low lateral mobility of once adsorbed DNA origami on the SiO2 surface, in combination with parasitic adsorption to the Au film. While parasitic adsorption can be suppressed by modifying the Au film with a hydrophobic self-assembled monolayer, the limited surface mobility of the adsorbed DNA origami still leads to poor localization accuracy in the nanoholes and results in many DNA origami crossing the boundary to the Au film even under optimized conditions. We discuss possible ways to minimize this effect by varying the composition of the adsorption buffer, employing different fabrication conditions, or using other substrate materials for nanohole array fabrication.

Effect of Dietary Sugar Intake on Biomarkers of Subclinical Inflammation: A Systematic Review and Meta-Analysis of Intervention Studies - Della Corte, Karen; Perrar, Ines; Penczynski, Katharina; Schwingshackl, Lukas; Herder, Christian; Buyken, Anette (Nutrients)

The relevance of restrained eating behavior for circadian eating patterns in adolescents - Koch, Stefanie A. J.; Alexy, Ute; Diederichs, Tanja; Buyken, Anette; Roßbach, Sarah (PLOS ONE)

Dietary Patterns in Primary School are of Prospective Relevance for the Development of Body Composition in Two German Pediatric Populations - Wolters, Maike; Joslowski, Gesa; Plachta-Danielzik, Sandra; Standl, Marie; Müller, Manfred; Ahrens, Wolfgang; Buyken, Anette (Nutrients)
This study performed comparative analyses in two pediatric cohorts to identify dietary patterns during primary school years and examined their relevance to body composition development. Nutritional and anthropometric data at the beginning of primary school and two or four years later were available from 298 and 372 participants of IDEFICS-Germany (Identification and prevention of Dietary-induced and lifestyle-induced health Effects In Children and infants Study) and the KOPS (Kiel Obesity Prevention Study) cohort, respectively. Principal component analyses (PCA) and reduced rank regression (RRR) were used to identify dietary patterns at baseline and patterns of change in food group intake during primary school years. RRR extracted patterns explaining variations in changes in body mass index (BMI), fat mass index (FMI), and waist-to-height-ratio (WtHR). Associations between pattern adherence and excess gain in BMI, FMI, or WtHR (>75th percentile) during primary school years were examined using logistic regression. Among PCA patterns, only a change towards a more Mediterranean food choice during primary school years were associated with a favorable body composition development in IDEFICS-Germany (p < 0.05). In KOPS, RRR patterns characterized by a frequent consumption of fast foods or starchy carbohydrate foods were consistently associated with an excess gain in BMI and WtHR (all p < 0.005). In IDEFICS-Germany, excess gain in BMI, FMI, and WtHR were predicted by a frequent consumption of nuts, meat, and pizza at baseline and a decrease in the consumption frequency of protein sources and snack carbohydrates during primary school years (all p < 0.01). The study confirms an adverse impact of fast food consumption on body composition during primary school years. Combinations of protein and carbohydrate sources deserve further investigation.

Network meta-analysis reaches nutrition research - Schwingshackl, Lukas; Buyken, Anette; Chaimani, Anna (European Journal of Nutrition)

Association between full breastfeeding, timing of complementary food introduction, and iron status in infancy in Germany: results of a secondary analysis of a randomized trial - Libuda, Lars; Hilbig, Annett; Berber-Al-Tawil, Seda; Kalhoff, Hermann; Kersting, Mathilde (European Journal of Nutrition)

The role of genetic variation of human metabolism for BMI, mental traits and mental disorders - Hebebrand, Johannes; Peters, Triinu; Schijven, Dick; Hebebrand, Moritz; Grasemann, Corinna; Winkler, Thomas W.; Heid, Iris M.; Antel, Jochen; Föcker, Manuel; Tegeler, Lisa; Brauner, Lena; Adan, Roger A.H.; et al. (Molecular Metabolism)

Effect of an vitamin D deficiency on depressive symptoms in child and adolescent psychiatric patients – a randomized controlled trial: study protocol - Föcker, Manuel; Antel, Jochen; Grasemann, Corinna; Führer, Dagmar; Timmesfeld, Nina; Öztürk, Dana; Peters, Triinu; Hinney, Anke; Hebebrand, Johannes; Libuda, Lars (BMC Psychiatry)

Peer Learning im Lehramtsstudium – Praxisbeispiel einer diversitysensiblen Lernbegleitung im Fach Hauswirtschaft - Hellweg, Joanna (Peer Learning an Hochschulen. Element einer diversitysensiblen, inklusiven Bildung)

Konsum, Ernährung und Gesundheit als zentrale Handlungsfelder für die alltägliche Lebensführung - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))
Der Artikel diskutiert zunächst Ziele, Aufgaben und Anforderungen an alltägliche Lebensführung und -gestaltung. Im Anschluss werden vor allem Wechselbeziehungen zwischen Entwicklungen und Strukturen in Wirtschaft, Gesellschaft und Politik einerseits und individueller Lebensführung andererseits betrachtet.

Das Lernzentrum Ernährung, Konsum, Gesundheit (LEKG) - Schlegel-Matthies, Kirsten; Hellweg, Joanna (Heterogenität als Chance. Bilanz und Perspektiven des Qualitätspakt Lehreprojekts an der Universität Paderborn)

„Keine Zeit!?“ – Über den Umgang mit einer kostbaren Ressource - Raacke, Georg (Alltägliche Lebensführung im Zusammenspiel von Individuum und Gesellschaft)
Zeit ist eine wichtige Ressource. Viele Menschen haben oft das Gefühl, die Zeit renne ihnen davon. Dabei ist Zeit auch immer eingebunden in gesellschaftliche Praxis. Während in der Vormoderne die Natur maßgeblich für die Bestimmung der Zeit war, brachte die Erfindung der Uhr ein völlig anderes Verständnis von Zeit und entsprechend von Zeithandeln. Zeit wurde nicht mehr als zyklisch verstanden, sondern als linearer Ablauf von Ereignissen. Heute gilt nicht mehr ausschließlich die Zeit der Uhr, Menschen sollen vielmehr flexibel ihre Zeit nutzen. Das hat nicht zuletzt eine unmittelbare Bedeutung für die alltägliche Lebensführung.

Polygene Formen der Adipositas und Störungs-übergreifende Analysen - Giuranna, J.; Antel, J.; Libuda, Lars; Reinehr, T.; Peters, T.; Hebebrand, J.; Hinney, A. (Adipositas - Ursachen, Folgeerkrankungen, Therapie)
Zusammenfassung Neben monogenen Formen und Hauptgen-Effekten sind für die genetische Prädisposition zur Adipositas polygene Mechanismen relevant. Meta-Analysen von genom-weiten Assoziationsstudien (GWAMA) haben mehr als 700 polygene Loci oder Polygene identifiziert, die genom-weit mit dem Body Mass index (BMI) assoziiert sind. Diese prädisponierenden Genvarianten (Allele) finden sich bei adipösen Probanden häufiger als bei normalgewichtigen oder schlanken Individuen. Mittels statistischer Analysen wurden diese Allele als Adipositas-Risikoallele klassifiziert. Jede einzelne polygene Variante leistet nur einen kleinen Beitrag zur Entwicklung einer Adipositas und erhöht das Gewicht pro Risikoallel nur um ca. hundert Gramm bis 1,5 Kilogramm. Der Erfolg der GWAMA hat in letzter Zeit Phänotyp übergreifende, sogenannte Cross- Disorder- und Cross-Phänotyp-Analysen, ermöglicht. Dabei können Risiko-Gene identifiziert werden, die mittels Analysen der einzelnen Erkrankungen / Phänotypen nicht entdeckt werden konnten. Funktionelle Studien (in vitro und in vivo) der GWAMA-abgeleiteten Polygene können zu einem besseren Verständnis der Mechanismen der Körpergewichtsregulation führen.

Trinken – was und wie viel? - Hilbig, A.; Libuda, Lars; Kalhoff, H. (Kinder- und Jugendmedizin)
Zusammenfassung Wasser ist für Menschen das wichtigste Nahrungsmittel. Die Verfügbarkeit von ausreichend Trinkwasser in hoher Qualität hat große Bedeutung und ist weltweit ein herausforderndes Entwicklungsziel. Wasser hat im Körper viele Funktionen, etwa als Baustoff, Reaktionsmedium und Reaktionspartner oder als wichtiges Transportmedium. Ein gut regulierter Wasserhaushalt ist Voraussetzung für normale Körperfunktionen und für langfristige Gesundheit. Eine Dehydratation kann zu Symptomen wie Schwäche, niedrigem Blutdruck und Hypotonie führen und die Bewusstseinslage beeinträchtigen. Ein vollständiger Wasserentzug ist schon nach Tagen tödlich. Aber auch eine leichte Dehydratation beeinträchtigt langfristig die körperliche und geistige Leistungsfähigkeit. Angaben zum täglichen Wasserbedarf stützen sich vornehmlich auf epidemiologisch ermittelte Zufuhrdaten, die für gesunde Kinder und Jugendliche adäquat sind. Im Durchschnitt sollten Schulkinder etwa einen Liter und Jugendliche etwa 1,5 Liter täglich trinken. Zuckergesüßte Getränke mit hoher Energiedichte könnten das Risiko für Übergewicht und Adipositas erhöhen. Ein gesunder Getränkeverzehr kann mit Maßnahmen zur Verhaltensund zur Verhältnisprävention gefördert werden.

Effects of breastfeeding on health outcomes in childhood: beyond dose-response relations - Buyken, Anette; Karaolis-Danckert, Nadina; Günther, Anke; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Habitual Flavonoid Intake from Fruit and Vegetables during Adolescence and Serum Lipid Levels in Early Adulthood: A Prospective Analysis - Penczynski, Katharina; Remer, Thomas; Herder, Christian; Kalhoff, Hermann; Rienks, Johanna; Markgraf, Daniel; Roden, Michael; Buyken, Anette (Nutrients)

In adolescence a higher ‘eveningness in energy intake’ is associated with higher total daily energy intake - Diederichs, Tanja; Perrar, Ines; Roßbach, Sarah; Alexy, Ute; Buyken, Anette (Appetite)

Positive Effects of Practical Nutrition Lessons in a Primary SchoolSetting with a High Proportion of Migrant School Children - Weber, Katharina S.; Eitner, Jessica; Dauben, Laura; Spörkel, Olaf; Strassburger, Klaus; Sommer, Jörn; Kaiser, Barbara; Buyken, Anette; Kronsbein, Peter; Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes)
Abstract Background Children with migration background are at increased risk for overweight, partly due to less favorable dietary habits compared to their German counterparts. We examined the effects of practical nutrition lessons among children with a high proportion of migration background in a primary school setting. Methods Ten 3rd and 4th grade classes (n=166 children, 73% with migration background) received the intervention and nine school classes (n=139 children, 76% with migration background) served as control. Before, shortly after (only among the intervention group) and three months after the three-day practical nutrition lessons, the nutrition-related skills, behavior, attitudes, and knowledge of the children were assessed using a questionnaire. Changes between baseline and 1st follow-up among children of the intervention group were calculated using linear mixed models. Differences between the two groups for changes between baseline and 2nd follow-up were tested using linear regression analyses. Models were adjusted for potential confounders. Results Shortly after the practical nutrition lessons, the children of the intervention group had improved their knowledge (β=1.7; 95% CI: 1.0; 2.4, P<0.001) and skills (β=1.8; 95% CI: 1.4; 2.2, P<0.001). These changes were sustainable and larger in the intervention compared to the control group (knowledge: β=1.6; 95% CI: 0.7; 2.5, P<0.001; skills: β=1.3; 95% CI: 0.7; 1.9, P<0.001). Changes in nutrition-related behavior and attitudes did not differ between the groups. Conclusions Providing practical nutrition lessons in a primary school setting with a high proportion of children with immigrational background improved the children’s nutrition-related knowledge and skills.

Time and age trends in morning and evening protein intakes of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Herder, Christian; Buyken, Anette; Alexy, Ute (Journal of Nutritional Science)
Abstract The present study describes time and age trends in morning and evening protein intakes and sources among German children and adolescents from 1985 to 2014. A total of 9757 three-day weighed dietary records of 1246 3- to 18-year-old participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were analysed using polynomial mixed-effects regression models. Morning protein intake increased over the study period by approximately 1 % of morning energy intake (linear trend P < 0·0001), with the youngest and the oldest children having the highest protein intake (linear, quadratic trend P < 0·0001). Evening protein intake increased over time by approximately 2 % of evening energy intake in girls (linear trend P < 0·0001) and 1 % of evening energy intake in boys (quadratic trend P = 0·0313), with decreasing intake with age (girls: linear trend P < 0·0001; boys: linear trend P = 0·0963). Time trends were largely due to increases in protein from ‘starchy foods’. In conclusion, morning and evening protein intakes increased modestly between 1985 and 2014; these increases were, however, not accompanied by increases in traditional protein sources (i.e. meat or dairy products).

Tomography and Purification of the Temporal-Mode Structure of Quantum Light - Ansari, Vahid; Donohue, John M.; Allgaier, Markus; Sansoni, Linda; Brecht, Benjamin; Roslund, Jonathan; Treps, Nicolas; Harder, Georg; Silberhorn, Christine (Physical Review Letters)

Tailoring nonlinear processes for quantum optics with pulsed temporal-mode encodings - Ansari, Vahid; Donohue, John M.; Brecht, Benjamin; Silberhorn, Christine (Optica)

Metasurface holography: from fundamentals to applications - Huang, Lingling; Zhang, Shuang; Zentgraf, Thomas (Nanophotonics)

Novel ALD Chemistry Enabled Low-Temperature Synthesis of Lithium Fluoride Coatings for Durable Lithium Anodes - Chen, Lin; Chen, Kan-Sheng; Chen, Xinjie; Ramirez, Giovanni; Huang, Zhennan; Geise, Natalie R.; Steinrück, Hans-Georg; Fisher, Brandon L.; Shahbazian-Yassar, Reza; Toney, Michael F.; Hersam, Mark C.; Elam, Jeffrey W. (ACS Applied Materials & Interfaces)

Fluoroethylene Carbonate Induces Ordered Electrolyte Interface on Silicon and Sapphire Surfaces as Revealed by Sum Frequency Generation Vibrational Spectroscopy and X-ray Reflectivity - Horowitz, Yonatan; Steinrück, Hans-Georg; Han, Hui-Ling; Cao, Chuntian; Abate, Iwnetim Iwnetu; Tsao, Yuchi; Toney, Michael F.; Somorjai, Gabor A. (Nano Letters)

The nanoscale structure of the electrolyte–metal oxide interface - Steinrück, Hans-Georg; Cao, Chuntian; Tsao, Yuchi; Takacs, Christopher J.; Konovalov, Oleg; Vatamanu, Jenel; Borodin, Oleg; Toney, Michael F. (Energy & Environmental Science)
Combined experimental and theoretical insights into electrolyte–electrode interfaces relevant to lithium ion batteries.

Surface structure evolution in a homologous series of ionic liquids - Haddad, Julia; Pontoni, Diego; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Steinrück, Hans-Georg; Reichert, Harald; Ocko, Benjamin M.; Deutsch, Moshe (Proceedings of the National Academy of Sciences)
Interfaces of room temperature ionic liquids (RTILs) are important for both applications and basic science and are therefore intensely studied. However, the evolution of their interface structure with the cation’s alkyl chain length n from Coulomb to van der Waals interaction domination has not yet been studied for even a single broad homologous RTIL series. We present here such a study of the liquid–air interface for n=2to 22 , using angstrom-resolution X-ray methods. For n<6 , a typical “simple liquid” monotonic surface-normal electron density profile ρe(z) is obtained, like those of water and organic solvents. For n>6 , increasingly more pronounced nanoscale self-segregation of the molecules’ charged moieties and apolar chains yields surface layering with alternating regions of headgroups and chains. The layering decays into the bulk over a few, to a few tens, of nanometers. The layering periods and decay lengths, their linear n dependence, and slopes are discussed within two models, one with partial-chain interdigitation and the other with liquid-like chains. No surface-parallel long-range order is found within the surface layer. For n=22 , a different surface phase is observed above melting. Our results also impact general liquid-phase issues like supramolecular self-aggregation and bulk–surface structure relations.